2018
DOI: 10.15405/epsbs.2018.12.03.8
|View full text |Cite
|
Sign up to set email alerts
|

The Application Towards Improving Notice Of Meeting Under Nigerian Company Law

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Janelle model, on its own, had explained that the basic factor is the increased demand for accessibility, occasioned by the introduction of transport systems and its spatial effect. Janelle’s model went further to show that this demand is a cyclic one, responding to new technology development and spatial reorganization of phenomena (Arowolo, 2008; Shamsuddeen, 1999). This study on the tricycle business has in a way found expression in both models but the cited models have failed to accommodate the current and future effects of the evolution and increasing use of this mode of transportation.…”
Section: The Tricycle Transportation Business: a Perspectivementioning
confidence: 99%
“…Janelle model, on its own, had explained that the basic factor is the increased demand for accessibility, occasioned by the introduction of transport systems and its spatial effect. Janelle’s model went further to show that this demand is a cyclic one, responding to new technology development and spatial reorganization of phenomena (Arowolo, 2008; Shamsuddeen, 1999). This study on the tricycle business has in a way found expression in both models but the cited models have failed to accommodate the current and future effects of the evolution and increasing use of this mode of transportation.…”
Section: The Tricycle Transportation Business: a Perspectivementioning
confidence: 99%